SISTEM PENDUKUNG KEPUTUSAN GURU BERPRESTASI MENGGUNAKAN METODE WEIGHTED PRODUCT - Dani, Dani; Anwar, A. Nurul (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
In accordance with the Law in Indonesia number 14 of 2005 regarding Lecturers and Teachers, namely Article 51 Paragraph (1) Point a, that is, teachers have the right to receive awards if they have had good performance in accordance with their performance. With the award will make the motivation, teachers become better, more productive, it can accelerate the development of the secondary education system in particular, and the development of national development in general. The election of outstanding teachers was held by the Principal of MTs Nafidatunnajah where PPMI was the source of HR information. Both from the Deputy Head of Curriculum, Student Affairs and School Public Relations, in obtaining supporting data. With this Weight Product Method as the process of selecting outstanding teachers. This web-based decision support system for selecting outstanding teachers using the Weight Product (WP) method is carried out by making six attributes as the basis for assessment, namely: discipline, attitude, teamwork, achievement, patience and appearance. With these 6 attributes, it is hoped that the selection of the best or outstanding teachers will be obtained. The concept or multiplication method that connects the ratings of the attributes used, where the attribute rating must be raised to the first rank with the weight of the attribute in question, thus the value obtained will be in accordance with what is expected because the weight on the attribute is determined by the assessment team in determine the best teacher <!–[if supportFields]>ADDIN CSL_CITATION "citationItems":["id":"ITEM-1","itemData":"author":["dropping-particle":"","family":"Pendukung","given":"Sistem","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Pemilihan","given":"Keputusan","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Dan","given":"Informatika","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Stmik","given":"Komputer","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Tuah","given":"Hang","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Mustafa","given":"Jalan","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"No","given":"Sari","non-dropping-particle":"","parse-names":false,"suffix":"","dropping-particle":"","family":"Selatan","given":"Tangkerang","non-dropping-particle":"","parse-names":false,"suffix":""],"id":"ITEM-1","issue":"1","issued":"date-parts":[["2019"]],"page":"13-20","title":"BERPRESTASI DI SEKOLAH TINGGI MANAJEMEN","type":"article-journal","volume":"11","uris":["http://www.mendeley.com/documents/?uuid=0b2e82a5-04e3-4ad3-a2e3-80571511aed5","http://www.mendeley.com/documents/?uuid=0d22a639-ce89-429a-86ca-bbc16002f72a"]],"mendeley":"formattedCitation":"(Pendukung et al., 2019)","manualFormatting":"(Hang, Mustafa., 2019)","plainTextFormattedCitation":"(Pendukung et al., 2019)","previouslyFormattedCitation":"(Pendukung et al., 2019)","properties":"noteIndex":0,"schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json"<![endif]–>(Hang, Mustafa., 2019)<!–[if supportFields]><![endif]–>.